2013
DOI: 10.1021/bi400283r
|View full text |Cite
|
Sign up to set email alerts
|

Structural Basis of Multisite Single-Stranded DNA Recognition and ACTA2 Repression by Purine-Rich Element Binding Protein B (Purβ)

Abstract: A hallmark of dysfunctional fibroblast to myofibroblast differentiation associated with fibrotic disorders is persistent expression of ACTA2, the gene encoding the cyto-contractile protein smooth muscle α-actin. In this study, a PURB-specific gene knockdown approach was used in conjunction with biochemical analyses of protein subdomain structure and function to reveal the mechanism by which purine-rich element binding protein B (Purβ) restricts ACTA2 expression in mouse embryo fibroblasts (MEFs). Consistent wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
99
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 14 publications
(103 citation statements)
references
References 67 publications
4
99
0
Order By: Relevance
“…Primers were selected using the QuikChange Primer Design Program (Supporting Information Table S1) and mutated plasmids were amplified using procedures specified by the manufacturer of the QuikChange II XL kit. Mixtures contained 1 μg of empty pCI plasmid or pCI-NHis-Purβ plasmid plus 0.9 μg of Acta2 promoterluciferase reporter plasmid (pVSMP8-Luc) 23 and 0.1 μg of pSV40-βGal control reporter plasmid. Mutated plasmids were isolated from bacterial host cells via double cesium chloride gradient centrifugation.…”
Section: Construction Of Expression Vectors Encoding Purβ Variantsmentioning
confidence: 99%
See 4 more Smart Citations
“…Primers were selected using the QuikChange Primer Design Program (Supporting Information Table S1) and mutated plasmids were amplified using procedures specified by the manufacturer of the QuikChange II XL kit. Mixtures contained 1 μg of empty pCI plasmid or pCI-NHis-Purβ plasmid plus 0.9 μg of Acta2 promoterluciferase reporter plasmid (pVSMP8-Luc) 23 and 0.1 μg of pSV40-βGal control reporter plasmid. Mutated plasmids were isolated from bacterial host cells via double cesium chloride gradient centrifugation.…”
Section: Construction Of Expression Vectors Encoding Purβ Variantsmentioning
confidence: 99%
“…16,18,19 Conversely, repression of Acta2 in fibroblasts appears to be governed by the purinerich element-binding proteins A and B (Purα and Purβ) and Y-box binding protein 1 (YB1), which bind in a strand-specific manner to DNA sequences that overlap the G/C-rich and MCAT elements. 22,23 The solved x-ray crystal structures of the truncated repeat I-II region of Drosophila melanogaster (Dm) Purα and fulllength Borrelia burgdorferi (Bb) Purα showed that certain β-strand and α-helix forming sequences located in each repeat associate to form a so-called PUR domain. 16,20 Insights into the specific molecular mechanism by which Purα and Purβ repress Acta2 have been provided by studies that have uncovered the unique structural features of each protein.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations